In Vitro Digestive Analysis of Digestible and Resistant Starch Fractions, with Concurrent Glycemic Index Determination, in Whole Grain Wheat Products Minimally Processed for Reduced Glycaemic Impact - John Monro; Suman Mishra (Foods, 2022)
Eight wheat products differing in texture (porridge vs. bread), grain fineness (fine, kibbled, intact), and cooking (raw vs. cooked), with pre-measured glycaemic indexes (GI), were analysed by in vitro amylolytic digestion to determine effects of processing to reduce GI on quantities of starch fractions differing in digestibility. The accuracy and precision of the in vitro analysis was assessed from its ability to concurrently predict clinical GI. In porridges, kernel intactness and lack of cooking reduced GI while increasing Type 1 (inaccessible) and Type 2 (ungelatinised) resistant starch. Porridge in vitro GI values (GIiv), calculated from the area under in vitro digestion curves minus estimated blood glucose disposal, were: raw fine, 26.3; raw kibbled, 12.6; cooked fine, 63.9; cooked kibbled, 44.1; and correlated closely with clinical GI values (R2 = 0.97). In bread, the negative association of kernel intactness and resistant starch with GI was seen in vitro but not in vivo. Bread GIiv values were: roller milled flour, 67.4; stoneground flour 61.1; kibbled grain, 53.0; kibbled + intact kernel, 49.5; but correlation with clinical values was low (R2 = 0.47), and variability in the clinical results was high (clinical CV = 72.5%, in vitro CV = 3.7%). Low glycaemic potency of wheat by minimal processing was achieved by maintaining particle size, avoiding hydrothermal treatment, avoiding crushing and using a food matrix requiring little chewing for ingestion. Use of in vitro digestive analysis for high precision measurement of starch fractions with potential secondary health benefits was validated by accurate concurrent prediction of the glycaemic index but needed to account for effects of chewing.